Piloting Penanggulangan Krisis Pangan Pada Masa Pandemi Covid-19 Melalui Optimalisasi Kawasan Rumah Pangan Lestari di Kelurahan Mugarsari dan Setiawargi Kota Tasikmalaya - Edi Fitriana Afriza; Andi Nur Rachman; Fuad Abdullah; Betanika Nila Nirbita (Journal of Appropriate Technology for Community Services, 2021)
The Covid-19 outbreak and the enactment of the "New Normal" era created a tentative situation, especially with limited food commodities for the needs of all people during times of food insecurity. Food products are limited in number and prices are increasingly soaring in the market, making people have a solution to resistance from the impact of the Covid-19 pandemic and the "New Normal" era, by realizing a sustainable food home area (KRPL), the community of housewives can meet their food needs, in addition to It is also a breakthrough that can provide an injection to the family economy if it is developed comprehensively. The activity will take place with the Asset Based Community Development (ABCD) approach focusing on the Family Welfare Empowerment (PKK) group where each group will be limited to 20 people / group, besides that the implementation of education and counseling will apply health protocols according to the direction of the central government. It is hoped that the realization of a sustainable food house area (KRPL) will provide stimulus and solutions to the community so that they can survive, be productive and be independent in this pandemic. Keywords: Food, Commodities, Asset Based Community Development (ABCD).